A preliminary investigation of the role of the transcription co-activators YAP/TAZ of the Hippo signalling pathway in canine and feline mammary tumours. (January 2016) - Beffagna, G.; Sacchetto, R.; Cavicchioli, L.; Sammarco, A.; Mainenti, M.; Ferro, S.; Trez, D.; Zulpo, M.; Michieletto, S.; Cecchinato, A.; Goldschmidt, M.; Zappulli, V.
Highlights: Evaluation of specificity and cross-reactivity of an anti-human YAP/TAZ antibody for dogs and cats. YAP and TAZ are expressed in canine and feline mammary tumours. Application and comparison of different scoring systems for immunohistochemistry. YAP/TAZ appears to be associated with aggressiveness and an undifferentiated phenotype of canine and feline mammary tumours. Abstract: Breast cancer is the most common cancer in women worldwide. Cancer metastases are responsible for the high mortality rate. A small but distinct subset of cells, cancer stem cells (CSCs), have the capacity to self-renew, initiate tumour formation, and develop metastases. The CSC content in human breast cancer correlates with the Hippo tumour suppressor signalling pathway. Specifically, the activity of YAP/TAZ, transcription co-activators of the Hippo pathway, sustains the self-renewal and tumour-initiation capacities of CSCs. Little is known about YAP/TAZ in canine and feline mammary tumours, which are very common tumours. The preliminary aim of the study was to investigate the expression of YAP/TAZ in canine and feline mammary tumours by Western blot and immunohistochemistry. Increased cytoplasmic and nuclear expression of YAP/TAZ was observed in all carcinomas compared to normal tissues, indicating neoplastic deregulation of the Hippo pathway. Nuclear expression significantly increased in grade III (high grade carcinomas) compared to grade I (low grade carcinomas) tumours, suggesting that YAP/TAZ play a role in the increased aggressiveness of these tumours. Moreover, different scoring systems for immunohistochemical analyses were compared and the H index and the Allred scores were the most significant. In conclusion, YAP/TAZ are expressed in aggressive canine and feline mammary tumours as reported in some human cancers. Further studies might better elucidate the role of the Hippo pathway in prognosis and as a target for new therapies. In addition, tumours in dogs and cats may be a useful model to study this pathway.